DEVELOPMENT DIGITAL OMIC USING PITON BASED OF MODEL PROBLEM BASED LEARNING (PBL) ON PPKN MATERIAL IN LASS VII JUNIOR HIGHT SCHOOL 10 AT SERANG ITY - Desi Ardianti; Ria Yuni Lestari; Wika Hardika Legiani (Journal Civics And Social Studies, 2023)
his researh as onduted to deelop digital omi learning media in the subjet of Panasila and itienship duation hih as arried out at unior ight hool 0 at erang ity. he purpose of deeloping digital omis is to help teahers in failitating teahers in learning atiities in the lassroom and to attrat students attention. his researh as onduted using the researh and deelopment method using the org all model hih has been modified by ugiono into stages of deelopment. pert alidation aims to determine the feasibility of the media arried out by to eperts, namely media eperts and material eperts, obtaining a sore of 0.00 from media eperts ho are ategoried as feasible and obtaining a alue of . from material eperts ho are inluded in the ery feasible ategory. rials ere held to find out the responses and assessments of students hih ere arried out on respondents ho obtained a sore of . hih an be ategoried as ery feasible learning media.